(untitled) (Nigerian Journal of Technology, 2018)
Retrial queues have been proposed in literature as a means of managing lost traffic in wireless cellular networks. However, the retrial queue system has led to a more complex Markovic process in network analysis. This complexity is further worsened by the addition of handover prioritization. In this paper, a solution that can minimize this complexity has been studied. The solution involves an integration of computational and analytical modeling techniques. The work was simulated and tested in Matlab/Simulink with guard channels as a handover prioritization scheme. Further evaluations were carried out on the effect of blocking probability (PB) as a quality of service (QoS) parameter. Numerical results obtained from the integrated approach show that the retrial queue reduces the PB for all requests (new and handover). The result obtained from this paper simplifies the solution to the complexity found in retrial queue systems. Furthermore, it was also deduced that reduced retrial rate with corresponding increase in the retrial queue size improves the network quality without an increase in system complexity. http://dx.doi.org/10.4314/njt.v37i2.16